BIPARTITE GRAPH ASSOCIATED WITH ELEMENTS AND COSETS OF SUBRINGS OF FINITE RINGS - Muhammad, Hubbi; Qonita, Niswah; Wahyu Fibriyanti, R A; Susanti, Yeni (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Let be a finite ring. The bipartite graph associated to elements and cosets of subrings of is a simple undirected graph with vertex set , where is the set of all subrings of , and two vertices and are adjacent if and only if In this study, we investigate some basic properties of the graph . In particular, we investigate some properties of , where is the ring of matrices over Also, we study the diameter of the bipartite graph associated to the quaternion ring